The Techification of Education in Ontario's virtual schools - RUTH NIELSEN (Canadian Society for Studies in Education, 2023)
In Ontario, Canada, the COVID-19 pandemic prompted the creation of publicly funded virtual schools for K-12, synchronous remote learning. Going into the 3rd year of operations, many of these schools are transitioning into permanent learning options. In this paper, I present preliminary findings from my doctoral research examining principals' leadership practices in these virtual schools. Qualitative interviews conducted in Spring 2022 reveal an emerging trend towards the techification of education: A phenomenon wherein Big Tech becomes enmeshed in all parts of education. Results show that virtual schools are increasingly relying on Google/Alphabet products in ways that may place schools as training grounds for lifetime consumer loyalty and may exacerbate existing inequities. I investigate this problem through the lens of school principals, as principals are a mediating point between policy and practice. Finally, I offer suggestions for how to mediate the techification of education at both the principal and policy level.